2010
DOI: 10.1159/000295898
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Antenatal Steroids on Fetal Lung Maturation between the 34th and 36th Week of Pregnancy

Abstract: Aim: To evaluate the effect of antenatal treatment with a single dose of betamethasone between the 34th and the 36th week of pregnancy on the maturation of fetal lung. Methods: To study 100 pregnant women in their 34th–36th week of pregnancy who were diagnosed as susceptible to have preterm delivery. Fifty patients did not receive betamethasone (group 1). The other 50 patients were administered 12 mg betamethasone in a single dose (group 2). Patients who delivered at least 24 h after the administration of beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 34 publications
1
56
2
1
Order By: Relevance
“…16,17 However, these studies were inconclusive as they were underpowered, 17 had substantial loss to follow-up, 16 and had post-randomization exclusions. 17 …”
Section: Discussionmentioning
confidence: 99%
“…16,17 However, these studies were inconclusive as they were underpowered, 17 had substantial loss to follow-up, 16 and had post-randomization exclusions. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Two smaller randomized trials have specifically assessed the use of betamethasone in the late preterm period to prevent adverse neonatal respiratory outcomes. 16,17 However, these studies were inconclusive as they were underpowered, 17 had substantial loss to follow-up, 16 and had post-randomization exclusions. 17 We found that infants exposed to antenatal betamethasone had a higher rate of neonatal hypoglycemia defined as glucose <40mg/dL.…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of fetal lung maturity might reduce the use of corticosteroids in late preterm deliveries (34 to 36 weeks of gestation), for which the risk of NRM is relevant but relatively low, ranging 10% to 20%. As recently shown, steroids decrease by one-third the occurrence of NRM in late preterm deliveries [8, 31- 34] and the number needed to treat to reduce one case of NRM in the circumstances described is 25 [8]. These findings have resulted in the publication of a Society for Maternal-Fetal Medicine statement on the use of antenatal corticosteroids in the late preterm period [35]; it recommends treatment under the strict inclusion criteria of the Antenatal Late Preterm Steriods study, while warning against overtreatment in those cases that do not meet the inclusion criteria.…”
Section: Commentmentioning
confidence: 99%